2016
DOI: 10.1159/000443056
|View full text |Cite
|
Sign up to set email alerts
|

ACE2 Antagonizes VEGFa to Reduce Vascular Permeability During Acute Lung Injury

Abstract: Background/Aims: Angiotensin converting enzyme 2 (ACE2) treatment suppresses the severity of acute lung injury (ALI), through antagonizing hydrolyzing angiotensin II (AngII) and the ALI-induced apoptosis of pulmonary endothelial cells. Nevertheless, the effects of ACE2 on vessel permeability and its relationship with vascular endothelial growth factor a (VEGFa) remain ill-defined. In the current study, we examined the relationship between ACE2 and VEGFa in ALI model in mice. Methods: Here, we used a previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…We found that Nrf2 knockdown in mice repressed NOX4, HIF-1α and VEGF expression after IIR, and Nrf2 upregulation by Sirt1 enhances NOX4, HIF-1α and VEGF expression after IIR in wild-type mice. HIF-1α is involved in the transcription of VEGF, which stimulates neovascularization following hypoxia or ischemia [26]. Wang et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…We found that Nrf2 knockdown in mice repressed NOX4, HIF-1α and VEGF expression after IIR, and Nrf2 upregulation by Sirt1 enhances NOX4, HIF-1α and VEGF expression after IIR in wild-type mice. HIF-1α is involved in the transcription of VEGF, which stimulates neovascularization following hypoxia or ischemia [26]. Wang et al [27].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, four ancillary variables were also used to assess the severe ARDS: radiographic severity, respiratory system compliance (≤40 mL/cm H 2 O), positive end-expiratory pressure (≥10 cm H 2 O), and corrected expired volume per minute (≥10 L/min) [1,2]. ARDS is characterized by massive inflammatory cell infiltration, increased capillary permeability, severe alveolar damage and the formation of hyaline membranes [3][4][5][6]. The primary insults leading to ARDS include microbial infection, pollutants, toxic gasses, gastric acids, autoantibodies, fatty emboli, free fatty acids and transfusion [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Circulating fibrocytes migrate to inflammatory or injured sites and participate in tissue healing or repair under inflammatory conditions [15-17]. Circulating fibrocytes release vascular endothelial growth factor (VEGF), cytokines and growth factors as well as activate fibroblasts to help the repair process [15, 18]. Circulating fibrocytes can differentiate into fibroblasts, osteoblasts and adipocytes [19, 20].…”
Section: Introductionmentioning
confidence: 99%